2022
DOI: 10.1186/s12943-022-01594-w
|View full text |Cite
|
Sign up to set email alerts
|

Letter to the Editor: An ultra-sensitive assay using cell-free DNA fragmentomics for multi-cancer early detection

Abstract: Early detection can benefit cancer patients with more effective treatments and better prognosis, but existing early screening tests are limited, especially for multi-cancer detection. This study investigated the most prevalent and lethal cancer types, including primary liver cancer (PLC), colorectal adenocarcinoma (CRC), and lung adenocarcinoma (LUAD). Leveraging the emerging cell-free DNA (cfDNA) fragmentomics, we developed a robust machine learning model for multi-cancer early detection. 1,214 participants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…The study of cfDNA fragmentation (Fragmentomics) is especially promising for the early detection of liver cancer [35 ▪▪ ], lung adenocarcinoma [36 ▪ ], advanced colorectal adenoma, and adenocarcinoma [37 ▪▪ ,38 ▪ ]. The circulating tumor DNA (ctDNA) fragments from cancer patients were shorter than the wild-type fragments from the healthy donors [39,40 ▪▪ ]. cfDNA fragmentation patterns reflect in vivo gene regulation across multiple molecular layers, such as nucleosome positioning and gene expression.…”
Section: Approaches In Biomarker Discovery and Developmentmentioning
confidence: 99%
“…The study of cfDNA fragmentation (Fragmentomics) is especially promising for the early detection of liver cancer [35 ▪▪ ], lung adenocarcinoma [36 ▪ ], advanced colorectal adenoma, and adenocarcinoma [37 ▪▪ ,38 ▪ ]. The circulating tumor DNA (ctDNA) fragments from cancer patients were shorter than the wild-type fragments from the healthy donors [39,40 ▪▪ ]. cfDNA fragmentation patterns reflect in vivo gene regulation across multiple molecular layers, such as nucleosome positioning and gene expression.…”
Section: Approaches In Biomarker Discovery and Developmentmentioning
confidence: 99%
“…circular versus linear DNA) [ 80 ]. These techniques have been useful in cancer detection as well as determining tissues of origin in cfDNA [ 81 , 82 ]. This could be integrated into the genomic analyses in CSF as another layer of information and assist in tumor detection, classification and monitoring of minimal residual disease because of its high sensitivity.…”
Section: Fragmentomicsmentioning
confidence: 99%
“…Plasma cfDNA fragmentomics is an emerging field that covers various features like fragment size, end point and nucleosome footprint, where many studies have demonstrated that significant difference could be observed between cancer patients and healthy individuals [ 9 12 ], even at early stages [ 13 16 ]. Cristiano et al introduced an approach focusing on the fragmentation size ratio in a multi-cancer cohort, in which the machine learning model had sensitivities of detection ranging from 57% to > 99% among seven cancer types at 98% specificity, with an overall AUC of 0.94 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%